Creating agrihood communities: exploring hybrid agriculture-focused residential development - Wulfkuhle, Madison (Kansas State University, 2022)
The general lack of knowledge and understanding of food systems has been a characteristic of urban and semi-urban residents of the United States since industrialization and reduction of the agrarian lifestyle. Less people are living in agricultural landscapes and society has shifted to a dependence on large scale industrial agriculture production. While urban agriculture has been explored widely in recent years, less attention has been paid to residential agriculture communities and a hybrid lifestyle. This study aims to address this issue by examining agriculture-focused residential developments. More specifically, this study investigates how residential agriculture typologies create a connection to food through a hybrid agrarian lifestyle. Precedent analysis were used to collect data from established urban agriculture communities across the United States. The study included analysis of common characteristics and themes within successful communities. Interviews with local realtors and developers then were conducted to understand the market interest for this type of development in Manhattan, Kansas. Our data analyses showed that successful agriculture-focused communities components included social/outreach opportunities, a focus on conservation and use of productive landscapes. We also found with many people wanting to be closer to local food there would be an interest in living in this type of community. These findings offer more insight into the connection between designed residential agriculture communities and our understanding of food systems, and contribute to the existing body of literature by identifying that urban agriculture can be used in this context to strengthen this connection. The broader outcome of this study highlights the role of residential agriculture communities in fostering a deeper understanding and connection to food production systems and the move towards a more hybrid agriculture-focused lifestyle.
Keywords: Agriculture-focused development; Peri-urban; Urban agriculture; Productive landscapes; Residential development; Hybrid lifestyle